Merancang Penelitian Tindakan Kelas (PTK) Bagi Guru Di SMA Negeri 3 Bungo - Despita Despita (PAKAR Pendidikan, 2014)
In order to increase the graduate competency, SMA N 3 Bungo has been consistent to make the improvement during the learning process. Various attempts were made as sustainable development for teachers, administrators, and all elements of the school. As a professional educator, teachers are managed to get a competence development. To increase the ability of teachers in education, teachers are developed to doing research in learning process. The main purpose of this article is a reference to enhance the capabilities of teachers in conducting action research, so the methods of this study can be applied in SMA N 3 Bungo. This article discusses the various alternative teaching methods and strategies for classroom action research that can be applied by teachers.